2019
DOI: 10.1037/emo0000517
|View full text |Cite
|
Sign up to set email alerts
|

Emotional expressions reduce the own-age bias.

Abstract: We are better at recognising faces of our own age group compared to faces of other age groups. It has been suggested that this own-age bias (OAB) might occur because of perceptual-expertise and/or social-cognitive mechanisms. While there is evidence to suggest effects of perceptual-expertise, little research has explored the role of social-cognitive factors. To do so, we looked at how the presence of an emotional expression on the face changes the magnitude of the OAB. Across three experiments young adult part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…It is, however, worth considering the implications of using the same image at learning and test for the interpretation of results. Prior research has demonstrated that the OAB is also observed when different images of the same individual are presented in the learning and test phases (Anastasi & Rhodes, ; Cronin, Craig, & Lipp, ; Harrison & Hole, ) so the presence of an OAB in the current study is unlikely to be affected by this methodological decision. The effectiveness of individuation instructions has, so far, only been demonstrated when using the same image at learning and test (Hugenberg et al ., ; Rhodes et al ., ; Young & Hugenberg, ; Young et al ., ).…”
Section: Discussionmentioning
confidence: 77%
“…It is, however, worth considering the implications of using the same image at learning and test for the interpretation of results. Prior research has demonstrated that the OAB is also observed when different images of the same individual are presented in the learning and test phases (Anastasi & Rhodes, ; Cronin, Craig, & Lipp, ; Harrison & Hole, ) so the presence of an OAB in the current study is unlikely to be affected by this methodological decision. The effectiveness of individuation instructions has, so far, only been demonstrated when using the same image at learning and test (Hugenberg et al ., ; Rhodes et al ., ; Young & Hugenberg, ; Young et al ., ).…”
Section: Discussionmentioning
confidence: 77%
“…A previously used intentional learning old/new recognition paradigm was employed (Cronin et al, 2019). Participants were randomly assigned to one of three stimulus list types: mixed, pure-young, or pure-old.…”
Section: Methodsmentioning
confidence: 99%
“…Those in the pureyoung condition saw 24 young faces, and those in the pure-old condition saw 24 older adult faces. In line with previous experiments investigating the OAB with online participants (Cronin et al, 2019), a secondary response time (RT) task was included to ensure participants were paying attention to the faces. To facilitate this, half of the faces were presented for 1,000 ms and half for 1,500 ms, with an inter-stimulus interval of 1,500 ms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations